Effect on Information Retrieval Using One and Two Point Crossover (International Journal of Engineering and Computer Science, 2018)
Information in digital world growing at very high speed. It is impossible to retrieve relevant and important information. To retrieve relevant information search engine is used. Genetic Algorithm and Information Retrieval System is used by search engine in order to retrieve relevant information. But retrieving information as user requirement is still difficult. In this paper information is retrieve using Genetic algorithm with one and two point crossover and cosine and Horng & Yeh similarity Function is used as fitness function in Genetic Algorithm.Keywords: Genetic Algorithm, One point crossover, Two point crossover, Information Retrieval, Vector Space Model, Database, Similarity Measure.